Моніторинг якості грунтів Рівненщини - Коваль, І. І. (НУБіП України, 2023)
Land monitoring is an important function of land use and protection management, the object of which is the land of Ukraine, regardless of land ownership, purpose and nature of use, in accordance with national and regional (local) programs. The soils of Rivne region require new approaches to developing ways to preserve, restore and increase soil fertility. After all, the acid reaction helps to weaken the synthesis of protein substances, while the content of proteins and total nitrogen decreases, and the amount of non-protein substances increases, inhibiting the process of converting monosugars into other, more complex, organic compounds.
Keywords: моніторинг якості грунтів; якість грунтів; monitoring of soil quality; Überwachung der Bodenqualität; Bodenqualität; soil quality